Pembelajaran Bahasa Indonesia dalam Kurikulum 2013 berbasis Teks yang Berorientasi pada Pendekatan Saintifik - Nur Mei Ningsih (Universitas Muhammadiyah Kotabumi, 2017)
Learning in the educational system can not be separated from the development of science and technology. The development of education notes that the era of the XXI Century there was a great shift on learning. Fundamental changes to access to information, computing, automation, and communication impact on the learning model of the XXI Century that directs learners into the focus of learning. Learners are conditioned actively so that the learning center is centered on the student centered. In the curriculum 2013 Indonesian language learning in text-based schools or more focused on the text. Text-based learning involves a process by which teachers help students produce text and gradually reduce aid so that students are able to produce text independently. Through these texts besides being taught linguistics also integrated character education. Especially through scientific or scientific approach, the formation of characters will be easily realized. In a scientific approach, students are asked to observe, question, try, associate, and communicate / summarize the core of the material related to learning Indonesian.